Moda Petrópolis: ressignificação por meio de análise gráfica, mapeamento de experiências e identidade visual - Costa, Alexandre Ribeiro (2019)
Considered by many as the largest open-air mall in Latin America, “Rua Teresa”, located in “Petrópolis”, is recognized for producing quality clothes with factory prices. Had, in its Golden times, 1.200 stores fully-functional. Nowadays, according to comparative statistics data, are 700—and the fashion street continues to struggle with the economy crisis effects by closing facilities as well as increasing the number of layoffs. As a response to this process, a new brand was presented to the public on November 8th, 2017, during the event“Aqui TemModa”, at the Rua Teresa’sFashion Center building: "Polo de Modas de Petrópolis". The proposal is to unite and integrate, in addition to “Rua Teresa”, two other shopping centers of the municipality focused on clothing—“Bingen” and “Feirinha de Itaipava”—in a unified symbol with the aim of strengthening the segment and local companies. Which factors, in terms of product or service communication, make it difficult to implement the "Polo de Moda Petrópolis" as a strategy to overcome the crisis in the Petrópolis' garment industry?